PELATIHAN KEBERSYUKURAN UNTUK MENINGKATKAN EMOSI POSITIF - Satria, Johan; Listiyandini, Ratih Arruum; Rahmatika, Rina; Kinanthi, Melok Roro (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
Training of gratitude is expected to grow these factors. Being grateful can lead to positive emotions that may create acceptance the conditions of self and positive social relationships. This training program was conducted for a full day, including induction and release of negative emotions, lesson about gratitude, mutual influence, contemplation, and pouring a sense of gratitude in writing. Training is given to 37 students of class X at SMKN 31 Jakarta. Pre and post test was conducted before and after training, using VAS (Visual Analog Scale) and PANAS (Positive affect-negative affect schedule). The effect of the training was analyzed by counting the change of mean from pre to post test score for each scale. The result showed that there are an increased of positive emotion score means after the training, from 6.92 to 7.41 for VAS and from 3.53 to 3.81 for PANAS score. Then it may concluded that the gratitude training program improve the positive emotion of the students.